Islamic Peril: Media and Global Violence by Karim H. Karim (Montréal: Black Rose, 2003. 208 pages.) (American Journal of Islam and Society, 2004)
At the junction of history, international relations, political science, andcommunication studies, Karim H. Karim’s Islamic Peril provides seriousand in-depth research on the media coverage of violence involving Muslimindividuals and groups. This updated edition of the book, first published in2000, adds a preface and an afterword that briefly account for 9/11 and itsaftermath. While studying the construction of Islam as the primary “Other”in Canada’s main print media since the beginning of the 1980s, the authorargues that the numerous (mis)representations and stereotypes of Muslimsare based on a lack of religious, sociological, political, and historicalknowledge rather than on what Karim calls a “centrally organized journalisticconspiracy against Islam” (p. 4).The author concentrates on the construction, flow, and reproductionof globally dominant interpretations through relations of power and dominationbetween the North and the South, but also inside the North’s media.His focus on journalism’s internal mechanisms (e.g., dependence on alimited number of sources, the need for simplification, and the clash ofinterests between information and business) and the wider sociopoliticaldomination processes (e.g., the end of the cold war or unipolarity) preventsthe analysis from being overtly simplistic and adopting a victimmentality. The author does not just highlight the (mis)representations; healso tries to analyze them. His approach is optimistic, for it implies thereis no fatality in reproducing stigmatization and stereotypes.Karim studies what could be called the “Islamization of representations”:the social construction of the linkage between facts of violence thatare historically and sociologically rooted and the notion of Islam as anessence. His analysis does not revolutionise the approach toward discourseson Islam, for one can feel how much he was influenced by the ...